Combined numerical approach for the evaluation of the energy efficiency and economic investment of building external insulation technologies - Matteo Venturelli; Roberto Saponelli; Massimo Milani; Luca Montorsi (Energy Nexus, 2023)
The objective of this paper is to examine the energy efficiency and economic feasibility of different coating technologies used to improve the thermal insulation of external walls in buildings. The comparison is made between traditional coat insulation and ventilated façade, evaluating their impact on energy consumption to maintain a constant indoor temperature throughout the year by means of a combined numerical approach. . Furthermore, the paper investigates the effect of opening and closing the air gap in ventilated façades on thermal insulation during the winter and summer seasons. Energy efficiency calculations are employed to estimate the economic investment required for implementing the different insulation solutions.The paper proposes an innovative combined approach to determine the performance of the building insulation technologies. Firstly, a computational fluid dynamics (CFD) simulation is carried out on the full three-dimensional geometry of the building during two reference days representing extreme temperature and sun radiation conditions during the summer and winter. This modeling includes the effects of solar radiative heat transfer during the day: for a chosen date, time, and geographical location, the model computes sun altitude and azimuthal angles, along with the corresponding direct and diffuse solar fluxes. In addition, the model uses a multiband thermal radiation approach to capture the different nature of radiative heat exchange according to the light wavelengths. The total heat transfer coefficient of the building walls in each scenario is calculated through the computational fluid dynamic analysis and implemented in an in-house developed library based on the open source Open-Modelica platform to simulate the energy requirement of the building throughout the year. This combined numerical approach provides a comprehensive performance analysis of the studied technologies in terms of electric energy and fuel consumption required for maintaining a constant indoor temperature and internal ambient comfort.The results of the simulations demonstrate that by adopting the two proposed solutions, there was a potential to save approximately 37% of the fuel required for the heating system and more than 51% of electric energy required for the air conditioning systems. Finally, the payback period for each scenario is calculated, and it was found that coat insulation offers the best balance between thermal performance improvement and economic effort, with a payback time close to 20 years.